Legally analysing and addressing the Effects of Ocean Acidification in a European Union law context through the lens of the Ecosystem Approach - Dreßler, Inken (UiT Norges arktiske universitet, 2023)
Ocean Acidification (OA) continues to have an increasing impact on the marine waters of the European Union (EU). Nevertheless, there is no legal framework in place that addresses OA sufficiently enough to reduce or even halt it. Therefore, it has become necessary to consider possible avenues and legal instruments that can tackle the consequences of OA. As the current sectorial approach to marine management has been unsuccessful in addressing complex issues such as OA, this paper set out to explore how and if the Ecosystem Approach, with a particular focus on adaptive management could contribute to tackling the consequences of OA within the marine waters of the EU. Following a concept analysis of the Ecosystem Approach and a subsequent case study on the utilisation of MPAs in response to the effects of OA, it must be concluded that no clear legal answer can be given.